IL17RA and IL21R polymorphisms influence type 1 diabetes predisposition and autoimmune phenotypes - Semzezem, Cintia; Gomes, Karla Fabiana Brasil; Santos, Aritania Sousa; Brochet, Pauline; Crisostomo, Lindiane Gomes; Correia, Marcia Regina Soares; Frade-Barros, Amanda Farage; Brito, Luciano Abreu; Passos-Bueno, Maria Rita; Chevillard, Christophe; Cunha-Neto, Edecio; da Silva, Maria Elizabeth Rossi (Frontiers in Endocrinology, 2025)
IntroductionAlthough interleukin receptors have been implicated in various autoimmune diseases, their role in type 1 diabetes (T1D) remains underexplored and occasionally inconsistent. To evaluate the impact of polymorphisms in genes encoding the interleukin receptors IL-21R and IL-17RA on T1D susceptibility and other autoimmune manifestations, we analyzed 639 patients with T1D and 653 healthy controls.MethodsSelected variants in IL17RA (n=4), IL21R (n=4), were genotyped using the VeraCode GoldenGate assay (Illumina, USA). Autoantibodies were assessed by radioimmunoassay, ELISA, and a radiolabeled iodine receptor assay.ResultsTwo IL17RA variants were significantly associated with T1D: the rs2241049G allele was linked to increased susceptibility (OR=1.42; p=0.005), whereas the rs879577A allele was related to protection (OR=0.61; p=0.021) and a reduced frequency of anti-tyrosine phosphatase (anti-IA2) autoantibody (OR= 0.52; p=0.010). Additionally, the rs5748863G allele was also associated with a lower frequency of anti-IA2 positivity (OR=0.52; p=0.010). Among IL21R variants, only rs7199138C was associated with an increased risk of T1D (OR=1.33; p=0.018). Moreover, rs2214537G and rs2285452A were linked to a reduced frequency of anti-parietal cell (OR=0.24; p<0.001) and anti-endomysium (OR=0.17; p=0.025) autoantibodies, respectively. In contrast, rs2285452A and rs3093315T were related to a higher frequency of anti-thyroperoxidase (OR=2.38; p=0.028) and TSH receptor (TRAb) autoantibodies (OR=5.90; p=0.024), respectively.DiscussionThese findings suggest that polymorphisms in IL17RA and IL21R genes may contribute to T1D pathogenesis and modulate the presence of pancreatic and extra-pancreatic autoantibodies.